Real-world EGFR testing practices for non-small-cell lung cancer by thoracic pathology laboratories across Europe - Hofman, Paul; Calabrese, F.; Kern, I.; Adam, J.; Alarcão, A.; Alborelli, I.; Anton, N. T.; Arndt, A.; Avdalyan, A.; Barberis, M.; Bégueret, H.; Bisig, B.; et al. (ESMO open, 2023)
BACKGROUND: Testing for epidermal growth factor receptor (EGFR) mutations is an essential recommendation in guidelines for metastatic non-squamous non-small-cell lung cancer, and is considered mandatory in European countries. However, in practice, challenges are often faced when carrying out routine biomarker testing, including access to testing, inadequate tissue samples and long turnaround times (TATs). - MATERIALS AND METHODS: To evaluate the real-world EGFR testing practices of European pathology laboratories, an online survey was set up and validated by the Pulmonary Pathology Working Group of the European Society of Pathology and distributed to 64 expert testing laboratories. The retrospective survey focussed on laboratory organisation and daily EGFR testing practice of pathologists and molecular biologists between 2018 and 2021. - RESULTS: TATs varied greatly both between and within countries. These discrepancies may be partly due to reflex testing practices, as 20.8% of laboratories carried out EGFR testing only at the request of the clinician. Many laboratories across Europe still favour single-test sequencing as a primary method of EGFR mutation identification; 32.7% indicated that they only used targeted techniques and 45.1% used single-gene testing followed by next-generation sequencing (NGS), depending on the case. Reported testing rates were consistent over time with no significant decrease in the number of EGFR tests carried out in 2020, despite the increased pressure faced by testing facilities during the COVID-19 pandemic. ISO 15189 accreditation was reported by 42.0% of molecular biology laboratories for single-test sequencing, and by 42.3% for NGS. 92.5% of laboratories indicated they regularly participate in an external quality assessment scheme. - CONCLUSIONS: These results highlight the strong heterogeneity of EGFR testing that still occurs within thoracic pathology and molecular biology laboratories across Europe. Even among expert testing facilities there is variability in testing capabilities, TAT, reflex testing practice and laboratory accreditation, stressing the need to harmonise reimbursement technologies and decision-making algorithms in Europe.
Gesehen am 06.11.2024